2016
DOI: 10.1038/srep30689
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-controlled radiation therapy was effective for treating a murine malignant melanoma cell line in vitro and in vivo

Abstract: Radiotherapy is a commonly used regimen for treating various types of intractable cancers, although the effects depend on the cell cycle of the targeted cancer cell lines, and for irradiation purposes it is therefore critical to establish a protocol for controlling the cell cycle. Here, we showed that a common murine melanoma cell line B16BL6 was more vulnerable to irradiation during the early S phase, and that synchronisation of the cell cycle greatly increased the therapeutic effects of radiotherapy. Cell-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 28 publications
4
41
1
Order By: Relevance
“…The phase of the tumor cell population can play a big role in radiation therapy as well. A recent study has shown higher radiosensitivity during the S/G2/M phase (Otani et al 2016). Based on the data in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The phase of the tumor cell population can play a big role in radiation therapy as well. A recent study has shown higher radiosensitivity during the S/G2/M phase (Otani et al 2016). Based on the data in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of cell synchronization using FUCCI induce the synchronization using methods including serum starvation, cell cycle-inhibiting drugs, environmental pH or contact inhibition [10][11][12][13][14][15]. Our assays are prepared using a standard method [10] normally thought to produce asynchronous populations, and we take utmost care to ensure that there is no induced synchronization in our cell cultures due to serum starvation, low pH or contact inhibition (electronic supplementary material, S1).…”
Section: Introductionmentioning
confidence: 99%
“…Harada et al introduced an EGFP-53BP1M FP probe to visualize the diversity of the radiation-induced DNA damage responses in real time [165]. Ishii's group reported that B16BL6 cells in the early S phase were the most susceptible to radiotherapy [166]. Live imaging technology using FPs is expected to make significant contributions to the direct visualization and detailed understanding of radiation adverse events.…”
Section: Biomed Research Internationalmentioning
confidence: 99%